Decreased nitric oxide levels in the hippocampus may play a role in learning and memory deficits in ovariectomized rats treated by a high dose of estradiol - Sadeghian, Reihaneh; Fereidoni, Masoud; Soukhtanloo, Mohammad; Azizi-Malekabadi, Hamid; Hosseini, Mahmoud (Arquivos de neuro-psiquiatria, 2012)
The effects of a high estradiol dose on memory and on nitric oxide metabolites in hippocampal tissues were investigated. Sham-Est and OVX-Est Groups were treated with 4 mg/kg of estradiol valerate for 12 weeks. Time latency and path length were significantly higher in the Sham-Est and OVX-Est Groups than in the Sham and OVX Groups, respectively (p<0.001). The animals in the Sham-Est and OVX-Est Groups spent lower time in the target quadrant (Q1) than those of the Sham and OVX Groups during the probe trial test (p<0.05 and <0.001, respectively). Significantly lower nitric oxide metabolite levels in the hippocampi of the Sham-Est and OVX-Est Groups were observed than in the Sham and OVX ones (p<0.001). These results suggest that decreased nitric oxide levels in the hippocampus may play a role in the learning and memory deficits observed after treatment with a high dose of estradiol, although the precise underlying mechanisms remain to be elucidated. Os efeitos de uma alta dose de estradiol na memória e nos metabólitos do óxido nítrico de tecidos hipocampais foram estudados. Os Grupos Sham-Est e OVX-Est foram tratados com 4 mg/kg de valerato de estradiol por 12 semanas. O tempo de latência e o comprimento do caminho foram significativamente maiores nos Grupos Sham-Est e OVX-Est em relação aos Grupos Sham e OVX, respectivamente (p<0,001). Os animais dos Grupos Sham-Est e OVX-Est passaram menos tempo na meta do quadrante (Q1) do que aqueles dos Grupos Sham e OVX durante o teste inicial (p<0,05 e <0,001, respectivamente). Níveis significativamente menores de metabólitos do óxido nítrico foram observados nos hipocampos dos Grupos Sham-Est e OVX-Est em relação aos Grupos Sham e OVX (p<0,001). Esses resultados sugerem que os níveis diminuídos de óxido nítrico no hipocampo podem ter um papel nos déficits de aprendizado e de memória, que são observados após tratamento com alta dose de estradiol, embora os mecanismos específicos envolvidos nestes achados ainda precisam ser elucidados.